Economía social y Covid-19: aportes y perspectivas en Colombia / Social economy and Covid-19: contributions and perspectives in Colombia - LORA OCHOA, Carmen; ANAYA NARVÁEZ, Alfredo; PINEDO LÓPEZ, Jhon (Utopía y Praxis Latinoamericana, 2020)
RESUMEN El propósito de este artículo es presentar los aportes de la economía social y su pertinencia en Colombia en época de pandemia. Es un trabajo investigativo de tipo documental, con enfoque descriptivo y propositivo, estructurado en tres secciones: 1) impacto del Covid 19 en el empleo, la informalidad y la pobreza; 2) aportes de la economía social antes del Covid-19; 3) pertinencia de la economía social en época de pandemia. El artículo concluye que la economía social es un modelo que aporta beneficios sociales, contribuye significativamente a la satisfacción de necesidades en época de crisis y puede constituirse en elemento fundamental para la solución de problemas estructurales en Colombia, evidenciados por la pandemia, que deben resolverse mediante la construcción de un nuevo pacto social. ABSTRACT The purpose of this article is to present the contributions of the social economy and its relevance in Colombia in times of pandemic. It is a documentary-type investigative work, with a descriptive and purposeful approach, structured in three sections: 1) impact of Covid-19 on employment, informality and poverty; 2) contributions from the social economy before Covid 19; 3) relevance of the social economy in times of pandemic. The article concludes that the social economy is a model that provides social benefits, contributes significantly to the satisfaction of needs in times of crisis and can become a fundamental element for solving Colombia’s structural problems, evidenced by the pandemic, which must be resolved through the construction of a new social pact.